Combinatorial Effects of Transcutaneous Spinal Stimulation and Task-Specific Training to Enhance Hand Motor Output after Paralysis. - Oh, Jeonghoon; Scheffler, Michelle S.; Mahan, Erin E.; King, Shane T.; Martin, Catherine A.; Dinh, Jenny; Steele, Alexander G.; O'Malley, Marcia K.; Sayenko, Dimitry G. (Topics in Spinal Cord Injury Rehabilitation)
Despite the positive results in upper limb (UL) motor recovery after using electrical neuromodulation in individuals after cervical spinal cord injury (SCI) or stroke, there has been limited exploration of potential benefits of combining task-specific hand grip training with transcutaneous electrical spinal stimulation (TSS) for individuals with UL paralysis. This study investigates the combinatorial effects of task-specific hand grip training and noninvasive TSS to enhance hand motor output after paralysis. Four participants with cervical SCI classified as AIS A and B and two participants with cerebral stroke were recruited in this study. The effects of cervical TSS without grip training and during training with sham stimulation were contrasted with hand grip training with TSS. TSS was applied at midline over cervical spinal cord. During hand grip training, 5 to 10 seconds of voluntary contraction were repeated at a submaximum strength for approximately 10 minutes, three days per week for 4 weeks. Signals from hand grip dynamometer along with the electromyography (EMG) activity from UL muscles were recorded and displayed as visual feedback. Our case study series demonstrated that combined task-specific hand grip training and cervical TSS targeting the motor pools of distal muscles in the UL resulted in significant improvements in maximum hand grip strength. However, TSS alone or hand grip training alone showed limited effectiveness in improving grip strength. Task-specific hand grip training combined with TSS can result in restoration of hand motor function in paralyzed upper limbs in individuals with cervical SCI and stroke.